SISTEM E-MARKETING PERUMAHAN MENGGUNAKAN FACEBOOK ADS SEBAGAI MEDIA SEGMENTASI PASAR (Sudi Kasus : PT. APR) - hadnan hardiansyah; Ananda (Politeknik Negeri Bengkalis, 2023)
The use of the internet is no stranger to marketing a product. An effort made to market products or services using internet media can also be called e-marketing. The rapid economic development of Riau Province has led to the need for housing in this area as well as continuing government programs in developing Riau in the future. Companies engaged in the field of Public Housing which focus on type 36. The company participated in the Government Program namely the Million Houses Program Based on data obtained from 200 home buyers at PT. Alam Prima Riau, for the most ages the filing of KPR is in the age range of 23-27 years. company PT. Alam Prima Riau the frequent occurrence of double booking is due to the absence of a system that handles the purchase of houses. The problem that is a problem for companies in terms of marketing is the limited marketing reach. To increase the marketing reach of property owned by the company, PT. Alam Prima Riau wants to build an online marketing tool using a website. In the process of marketing target segmentation based on age, the author uses facebook e-marketing property system using promotion tools to help communicate the company's promotional goals through websites, social media and through consumers of PT. Alam Prima Riau. In the targeting process, the author uses facebook ads as a media segmentation based on the age and domicile of prospective consumers to get the target potential customers. Based on the results of the blackbox test conducted by admin and customers, the features of a residential e-marketing system are made running with a 100% success rate.